2006
DOI: 10.1055/s-2006-923875
|View full text |Cite
|
Sign up to set email alerts
|

Sectio caesarea bei fulminanter Lungenembolie und nachfolgende Lysetherapie - Ein Fallbericht

Abstract: Thromboembolien in der Schwangerschaft und in der frühen postpartalen Phase gehören in den westeuropäischen Staaten zu den Hauptursachen mütterlicher Morbidität und Mortalität [5,13,18, 20]. Aussagen zur Inzidenz dieser schwer wiegenden Erkrankung während der Schwangerschaft variieren zwischen 0,013 und 0,3%, hierbei wird die Letalität infolge einer Lungenembolie mit 1 pro 100 000 Schwangerschaften angegeben [6]. Wir beschreiben den Verlauf einer fulminanten Lungenembolie bei einer 35-jährigen Drittgebärenden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Cochak et al (2021) reported a high density of these predators on day 19 of the same experiment, which supports our assumption. This idea is further supported by studies conducted in other aquatic environments, where ciliates and zooplankton selectively suppressed a signi cant portion of the algal biomass (Sommer et al 2006;Posch et al 2015;Drira et al 2018). Laboratory experiments also provide evidence for this assumption (Pérez et al 1997;Khemakhem et al 2010).…”
Section: Discussionmentioning
confidence: 55%
“…Cochak et al (2021) reported a high density of these predators on day 19 of the same experiment, which supports our assumption. This idea is further supported by studies conducted in other aquatic environments, where ciliates and zooplankton selectively suppressed a signi cant portion of the algal biomass (Sommer et al 2006;Posch et al 2015;Drira et al 2018). Laboratory experiments also provide evidence for this assumption (Pérez et al 1997;Khemakhem et al 2010).…”
Section: Discussionmentioning
confidence: 55%